Maqashid Sharia Perspective and the Opportunity of Blue Sukuk for Sustainable Development Goals in Indonesia - Dina Diana (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
This study aims to examining how Islam can contribute to the protection of the environment by exploring the maqashid sharia approach. It also investigates the potential of using blue sukuk investments in managing marine ecosystems to attain sustainable development goals in Indonesia. The concept of hifdh al-'alam or environmental protection is an integral part of maqashid al-sharia, which aims to safeguard all living creatures. This aligns with sustainable development goals number 14, which focuses on preserving the ocean ecosystem. The management of marine fishing in Indonesia poses several challenges that jeopardize the sustainability of fish resources, livelihoods, food security, and economic growth. To address these issues, there is a significant need for financing instruments to develop the marine sector. Blue sukuk provides an opportunity to finance this sector. The development of regulatory aspects, feasible underlying projects, investors, and inter-institutional coordination are critical for the successful implementation of blue sukuk. Key stakeholders with interests in blue sukuk are the government, investors, and fishery communities. Islamic financial institutions and mechanisms may play a significant role in the issuance and development of blue sukuk in Indonesia in the future.